2016
DOI: 10.1038/mp.2016.182
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial peptidoglycan-sensing molecule Pglyrp2 modulates brain development and behavior

Abstract: Recent studies have revealed that the gut microbiota modulates brain development and behavior, but the underlying mechanisms are still poorly understood. Here, we show that bacterial peptidoglycan (PGN) derived from the commensal gut microbiota can be translocated into the brain and sensed by specific pattern-recognition receptors (PRRs) of the innate immune system. Using expression-profiling techniques, we demonstrate that two families of PRRs that specifically detect PGN (that is, PGN-recognition proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
172
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(181 citation statements)
references
References 54 publications
7
172
0
2
Order By: Relevance
“…Furthermore, epidemiological studies have discovered a strong relationship between vascular risks and depression (Valkanova and Ebmeier, 2013). In parallel, recent findings indicate that gut microbiota-derived molecules can also translocate into the brain and have life stage- as well as brain region-specific effects on the striatum (Arentsen et al, 2017; Diaz Heijtz et al, 2011). Thus, region-specific neurovascular interaction may have a unique role in the development and function of brain reward circuitry and, as a result, implications for a large number of neuropsychiatric diseases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, epidemiological studies have discovered a strong relationship between vascular risks and depression (Valkanova and Ebmeier, 2013). In parallel, recent findings indicate that gut microbiota-derived molecules can also translocate into the brain and have life stage- as well as brain region-specific effects on the striatum (Arentsen et al, 2017; Diaz Heijtz et al, 2011). Thus, region-specific neurovascular interaction may have a unique role in the development and function of brain reward circuitry and, as a result, implications for a large number of neuropsychiatric diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, many striatum-based neurobiological processes are strongly influenced by blood-borne endocrine signals (Jang et al, 2013; Mak et al, 2007; Moaddab et al, 2015; Schoffelmeer et al, 2011), especially during early life (Lajud et al, 2013; Miller and Caldwell, 2015; Panagopoulos and Ralevski, 2014), and by vascular risk factors (Valkanova and Ebmeier, 2013), suggesting a unique role of regional vasculature. Gut microbiota-derived molecules have also been found to translocate into the brain and exert stage- and region-specific impacts on striatum (Arentsen et al, 2017; Diaz Heijtz et al, 2011). Thus, understanding GM angiogenesis may not only provide insights into mechanisms of region-specific neurovascular communication and GM hemorrhage, but may also have implications for understanding brain reward circuit development and function.…”
Section: Introductionmentioning
confidence: 99%
“…However, emerging studies are providing some insight into the mechanisms underlying how gut bacteria influence social behaviors. In a recent study from the Karolinska Institute, the authors identify a role for bacterial‐sensing molecules in regulating social development . Genetic knockdown of the peptidoglycan‐sensing molecule PGLYRP2 was found to increase social behaviors in both male and female mice in the three‐chamber test while also modulating the expression of genes related to synaptic plasticity .…”
Section: Moving Toward Mechanismsmentioning
confidence: 99%
“…In a recent study from the Karolinska Institute, the authors identify a role for bacterial‐sensing molecules in regulating social development . Genetic knockdown of the peptidoglycan‐sensing molecule PGLYRP2 was found to increase social behaviors in both male and female mice in the three‐chamber test while also modulating the expression of genes related to synaptic plasticity . The authors argue that bacterial components, such as peptidoglycan, cross the blood–brain barrier during postnatal development and bind to molecules, such as PGLYRP2, to influence neuronal circuits linked to social behaviors …”
Section: Moving Toward Mechanismsmentioning
confidence: 99%
“…For example, in 1 study, bacterial peptidoglycan (PGN) was derived from the commensal gut microbiota and it was shown that PGN was able to translocate into the brain and was sensed by specific patternrecognition receptors within the innate immune system. 40 Furthermore, the absence of these bacterial factors was associated with increased risk for autism-like behavior in a mouse model. Similarly, in mice, polysaccharide A from the capsule of the commensal bacterium Bacteroides fragilis was protective of experimental autoimmune encephalomyelitis, which is the experimental model of human multiple sclerosis.…”
Section: Examples Of Gut-brain Axis Interactions Across Animal Modelsmentioning
confidence: 99%